Uma abordagem da gravidade entrópica na cosmologia - Matias, Rayanne Moreira (2022)
In the present work we approach the model of entropic gravity in which recent theoretical progress indicates that spacetime and gravity emerge together from the entanglement structure of an underlying microscopic theory. We use the Anti-de Sitter space to better deal with these ideas, where they depend on the area law for entanglement entropy. For this purpose, we first review thermodynamics, then an introduction to emergent gravity through topics of general relativity, with Einstein’s equations. Finally, using insights from black hole physics and quantum information theory, we argue that positive dark energy leads to a contribution of the thermal volume law to entropy that surpasses the area law precisely at the cosmological horizon. From the work of Erik Verlinde, we draw on his arguments that the emergent laws of gravity contain an additional dark gravitational force that describes the elastic response due to the entropy shift. We derive an estimate of the extra force in terms of baryonic matter, Newton’s constant, and Hubble’s acceleration scale, a0 = cH0, these provide evidence for the fact that this dark gravity force further explains the phenomena observed in galaxies and clusters currently attributed to dark matter.